2022
DOI: 10.7189/jogh.12.04048
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluations of mammography to screen for breast cancer in low- and middle-income countries: A systematic review

Abstract: review identified 21 studies economically evaluating mammography as a breast cancer screening method in LMICs. Eighteen of these studies concluded that mammography screening was a cost-effective strategy. Most studies (71%) were conducted in upper-middle-income countries (Upper MICs). The quality of the studies varied from low to good. Important factors determining cost-effectiveness are the target age group (eg, 50-59 years), the screening interval (eg, biennial or triennial), as well as any combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…One of the most challenging for early breast cancer detection is the cost of screening ( 4 ). A systematic review has found that mammography is a cost-effective breast cancer screening method in LMICs in Asia, especially in upper-middle-income countries with the target population of 50–59 years ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most challenging for early breast cancer detection is the cost of screening ( 4 ). A systematic review has found that mammography is a cost-effective breast cancer screening method in LMICs in Asia, especially in upper-middle-income countries with the target population of 50–59 years ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…(7,8) Digital mammography has been studied as a cost-efficient method of breast cancer screening especially for population < 50 years old and for asymptomatic women with average risk for breast cancer. (9,10) Digital mammography was found to have a 97% sensitivity and 64.5% specificity when compared to histopathology as a gold standard. (11) The latest study in Netherlands stated that the use of biennial digital mammography is still more costeffective than the use of digital breast tomosynthesis for a certain maximum threshold per life-year gained.…”
Section: Introductionmentioning
confidence: 98%
“…As is well known, on the one hand, the breast cancer mammography screening strategy by population-based had been widely implemented in developed regions for few decades. A systematic review reported eighteen researches reported that breast cancer screening by mammography was regarded as a cost-effective strategy and almost 70% researches were implemented in upper income and middle income regions 19 . On the other hand, perhaps because of less developed regions have limited resources compared to developed regions, whether the breast cancer screening by mammography could be effective and cost-effectiveness is still unclear, and even an intractable problem 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%